The Convincing Ground, Portland Bay, Victoria, Australia: An Exploration of the Controversy Surrounding its Onomastic History. (March 2014) - Clark, Ian D.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents the results of a case study into the historiography of the Convincing Ground toponym at Portland Bay, Victoria, Australia. This study shows that research by Connor (2005a) into the usage of the phrase "convincing ground" in nineteenth-century Australia is superficial, and his preference for one explanation of the origin of the Convincing Ground toponym that relates to intra-whaler conflict resolution is superficial and inadequate. This analysis supports the alternative narrative that the toponym has its origin in a dispute between whalers and Aborigines over possession of a beached whale. Furthermore, Connor failed to consider the possibility that the phrase "convincing ground" is polysemous, which means that we should not expect to find a singular homogenous explanation or application in the literature. He also failed to discuss the real possibility that the Convincing Ground may also be a onomastic palimpsest and that both the Aboriginal-whaler dispute narrative and the intra-whaler dispute narrative may be legitimate explanations relevant at particular moments in the place's history.